Learn Aspen Plus in 24 Hours, Second Edition - Adams, Thomas A. (McGraw-Hill's AccessEngineering., 2022)
Discover how to solve chemical engineering problems with Aspen Plus? in just 24 hours, with no prior experience. Thoroughly revised for the latest distribution, this self-learning guide features detailed mathematical models for a wide range of chemical process equipment, including heat exchangers, pumps, compressors, turbines, distillation columns, and chemical reactors. Divided into 12 two-hour lessons, Learn Aspen Plus? in 24 Hours, Second Edition shows, step by step, how to build process models and simulations without performing tedious calculations. You will also get downloadable Aspen Plus simulation files and helpful quick starter templates.